2022
DOI: 10.3390/cancers14215432
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Safety of Single-Probe Cryoablation with Liquid Nitrogen: An Initial Experience in 24 Various Tumor Lesions

Abstract: Background: Percutaneous cryoablation with liquid nitrogen is a new technique being used in the treatment of some malignant tumors. Our objective was to assess its feasibility in the ablation of tumor lesions of various sizes and locations. Methods: This retrospective, monocentric study included all consecutive patients who underwent percutaneous cryoablation with liquid nitrogen between December 2019 and March 2021. Cryoablation was performed using 10G or 13G cryoprobes. The ablation volume was measured on po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Detected hematomas in our study were solely identified on CT, and none presented clinical relevance or necessitated transfusion. In a prior study involving 22 patients treated across various organs using the same device, no significant complications were reported, particularly concerning bleeding [14]. Some operators, due to anticipated risks, opted to embolize the puncture path utilizing resorbable gelatin or glue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detected hematomas in our study were solely identified on CT, and none presented clinical relevance or necessitated transfusion. In a prior study involving 22 patients treated across various organs using the same device, no significant complications were reported, particularly concerning bleeding [14]. Some operators, due to anticipated risks, opted to embolize the puncture path utilizing resorbable gelatin or glue.…”
Section: Discussionmentioning
confidence: 99%
“…The safety and effectiveness of this equipment have been documented in a randomized clinical trial focused on the treatment of low-grade breast cancers [13]. This innovation paves the way for potential treatments across a wider range of organs [14,15].…”
Section: Introductionmentioning
confidence: 99%